Penurunan Depresi Pada Difabel Akibat Kecelakaan Melalui Pelatihan Ketrampilan Regulasi Emosi - Setyowati, Rini, Dr. Nisa Rachmah N.A., M.Si., Psi, Setia Asyanti S.Psi., M.Si., Psi (2015)
This study examined the effect of emotion regulation skills training in reducing depression on disability due to an accident. This study used a nonrandomized design pretest-posttest control group and there were 12 subject consisted of 6 experimental group and 6 control group. Beck Depression Inventory (BDI) was used to measure the level of depression before treatment, after treatment and follow-up. Based on the results of quantitative analysis with statistical test nonparametric Mann-Whitney U, the result showed there were differences in decreased depression in the experimental group were given training in comparison with the control group, Wilcoxon T, the result showed there were significant differences between the scores of depression before and after training the experimental group. Qualitative data also supported quantitative analysis, that emotion regulation skills in the subjects of the experiment increased after training. Thus, it can be concluded that the emotion regulation skills training was effective in reducing depression in disabilities due to accidents. Therefore, thistrainingprogramcan be usedas a therapyin order to overcomedepressionondisabilitydue to an accident.